ANTIBACTERIAL ACTIVITY OF SILVER NANOCOLLOID GEL BIOSINTHESIZED BY Alocasia macrorrhizos PLANT EXTRACT AGAINST Staphylococcus aureus : UJI AKTIVITAS ANTIBAKTERI GEL NANOKOLOID PERAK HASIL BIOSINTESIS MENGGUNAKAN EKSTRAK TANAMAN KELADI SARAWAK (Alocasia macrorrhizos (L.)) TERHADAP BAKTERI Staphylococcus aureus - Athiah Masykuroh; Ika Ristia Rahman; Hairunnisa; Nine Okta Meliadlina; Putry Fajaria Hardiani (BIOMA : JURNAL BIOLOGI MAKASSAR, 2024)
An antibacterial activity test has been conducted against Staphylococcus aureus bacteria on silver nanocolloids gel biosynthesized using Alocasia macrorrhizos plant extract which contains phenolic derivative compounds : polyphenols, flavonoids and cyanogenic glycosides. The AgNO3 concentration used in the silver nanocolloid biosynthesis process is 0.05 M;0,10 M and 0,15 M. The silver nanocolloids was diluted in the amount of 50% from the previous concentration and innovated into a gel form (formula I, II and III) then tested on Staphylococcus aureus bacteria. The measurement of of the clear zone formed around the disc paper was carried out to determine it’s antibacterial activity. Only the third variation meet the requirements of the physical evaluation test results as a gel form. All concentrations of silver nanocolloid gel preparations can inhibit the growth of Staphylococcus aureus bacteria as shown in observations obtained by the average diameter of the inhibition zone for formula I of 12.55 mm, formula II of 12.64 mm and formula III of 12.71 mm which is the zone of resistance formed was induced strong category (10-20 mm). The significance value with the One way ANOVA test is 0.000 (p<0.05), means that the average value of each variation is significantly different.